Gamma interferon induces rapid and coordinate activation of mitogen-activated protein kinase (extracellular signal-regulated kinase) and calcium-independent protein kinase C in human monocytes. - Liu, M K (1994)
Gamma interferon plays an important role in regulating the functional properties of mononuclear phagocytes. In the present study, the role of activated protein kinases in the mechanism of action of gamma interferon cell signaling in human peripheral blood monocytes was investigated. Analysis in vitro of 100,000 x g cytosolic fractions from untreated and interferon-treated cells showed that agonist treatment resulted in time- and concentration-dependent increases in phosphotransferase activity when myelin basic protein (MBP) was used as the substrate. Anion-exchange chromatography of high-speed supernatants prepared from detergent extracts of interferon-treated cells revealed two discrete peaks of MBP phosphotransferase activity. Immunoblotting of fractions from these peaks with antiphosphotyrosine antibodies and with antibodies that specifically recognize the family of mitogen-activated protein (MAP) kinases detected a MAP kinase with a subunit M(r) of 42,000 in the earliest-eluting peak (peak 1). Phosphorylation of the 42,000-M(r) protein on tyrosine was observed only after treatment of cells with interferon. The contribution of MAP kinase to the interferon-stimulated activity in peak 1 was confirmed by quantitative immunoprecipitation with anti-MAP kinase and antiphosphotyrosine antibodies. The conclusion that the interferon-activated MBP kinase in peak 1 could be accounted for by an activated MAP kinase was also supported by the finding that fractions from Mono Q peak 1 demonstrated activity towards a MAP kinase-specific substrate. The later-eluting peak of interferon-activated MBP phosphotransferase activity appeared to be accounted for by an activated protein kinase C (PKC). This conclusion is based upon analyses of immunoblotting and immunoprecipitation experiments with antibodies to PKC and was also supported by the observed inhibition of this kinase with a PKC pseudosubstrate peptide. The interferon-stimulated PKC present in Mono Q peak 2 was active in the absence of calcium ions, suggesting that it is a calcium-independent isoform of PKC.